Colorimetric detection of cadmium in water using L-cysteine Functionalized gold–silver nanoparticles. (12th December 2018) - Du, Jiawei; Hu, Xing; Zhang, Guowen; Wu, Xiaqing; Gong, Deming
Abstract: A new simple colorimetric assay was developed for the selective and sensitive detection of cadmium (II) in water samples using L -cysteine functionalized gold–silver nanoparticles. The gold–silver nanoparticles were synthesized by reducing HAuCl4 and AgNO3 in aqueous medium and were further functionalized with L -cysteine. The formation of homogeneous gold–silver nanoparticles was characterized by transmission electron microscopy, energy-dispersive X-ray spectroscopy, particle size distribution, and ultraviolet–visible absorption methods. In the presence of cadmium (II), the aggregation of functionalized gold–silver nanoparticles caused by the interaction between cadmium (II) and L -cysteine resulted in a naked-eye visible color change of L -cysteine functionalized gold–silver nanoparticles from orange–yellow to green, which can be monitored by a simple ultraviolet–visible spectrophotometer. Under the optimal conditions, the absorbance ratio at 600–435 nm ( A 600 / A 435 ) was linear to the concentration of cadmium (II) from 0.4 to 38.6 μM, and the limit of detection of cadmium (II) was 44 nM. Interference measurements showed that the method exhibited good selectivity. The proposed method was successfully applied to the determination of cadmium (II) in environmental water samples. The results indicated that this simple, selective, and sensitive sensing system has good potential for practical applications.